2021
DOI: 10.1371/journal.pcbi.1009097
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based modeling of the central amygdala and pain using cell-type specific physiological parameters

Abstract: The amygdala is a brain area involved in emotional regulation and pain. Over the course of the last 20 years, multiple researchers have studied sensory and motor connections within the amygdala in trying to understand the ultimate role of this structure in pain perception and descending control of pain. A number of investigators have been using cell-type specific manipulations to probe the underlying circuitry of the amygdala. As data have accumulated in this research space, we recognized a critical need for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Evidence for central processes beyond local pathophysiology has been accumulating, including recent studies demonstrating that chronic pain is best conceptualized as a combination of biopsychosocial factors that may lead to a variety of pain conditions [21, 125, 75, 20, 124, 16]. Studies in rodents have identified neuroinflammation- and neuroplasticity-related changes in brain pathways that mediate persistent pain behavior in animal models of different pain modalities [143, 96, 91, 27, 6, 122, 52, 5, 37, 87]. Neuroimaging studies have identified common brain systems involved in musculoskeletal pain [79, 68, 17, 44, 67, 61, 90], IBS [106, 4], orofacial pain [2], neuropathic pain [95, 100, 139], and postsurgical pain [47].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for central processes beyond local pathophysiology has been accumulating, including recent studies demonstrating that chronic pain is best conceptualized as a combination of biopsychosocial factors that may lead to a variety of pain conditions [21, 125, 75, 20, 124, 16]. Studies in rodents have identified neuroinflammation- and neuroplasticity-related changes in brain pathways that mediate persistent pain behavior in animal models of different pain modalities [143, 96, 91, 27, 6, 122, 52, 5, 37, 87]. Neuroimaging studies have identified common brain systems involved in musculoskeletal pain [79, 68, 17, 44, 67, 61, 90], IBS [106, 4], orofacial pain [2], neuropathic pain [95, 100, 139], and postsurgical pain [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mostly used the expression of a specific neurochemical marker for the base of cell type identification in amygdala. These markers include SOM, PKCδ, CRF, neurotensin and tachykinin ( Li et al, 2013 ; Hunt et al, 2017 ; McCullough et al, 2018 ; Wilson et al, 2019 ; Li and Sheets, 2020 ; Miller Neilan et al, 2021 ). For example, PBN has been shown to project to both SOM-expressing [SOM(+)] and CRH(+) CeA cells ( Li and Sheets, 2020 ); optical activation of PKCδ(+) or CRH(+) CeA cells increases pain response whereas optical activation of SOM(+) CeA cells decreases pain response under pain conditions ( Wilson et al, 2019 ; Mazzitelli et al, 2021 ; Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that there are functionally distinct types of cells in CeA that mediate differential effects on pain ( Wilson et al, 2019 ; Li and Sheets, 2020 ; Neugebauer et al, 2020 ; Miller Neilan et al, 2021 ). These previous studies primarily focus on CeA cells that express different neurochemical profiles of somatostatin (SOM), protein kinase C-delta (PKCδ) or corticotropin-releasing hormone (CRF) in regulation of pain.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in and need for artificial enzymes [ 1 , 2 ]. Although researchers have explored many experimental and computational methods for elucidating the chemical mechanisms of enzymes, most of these sophisticated methods are for noninvasive observation [ 3 ]. To study the catalytically competent state of an enzyme, researchers routinely use a substrate or inhibitor as an interloper to bind the active site [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers have explored many experimental and computational methods for elucidating the chemical mechanisms of enzymes, most of these sophisticated methods are for noninvasive observation [ 3 ]. To study the catalytically competent state of an enzyme, researchers routinely use a substrate or inhibitor as an interloper to bind the active site [ 3 ]. Notable exceptions to this reliance on substrates and inhibitors involve the use of mechanical force or miniaturized tweezers [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%